Outcome of critically ill patients receiving systemic chemotherapy on the intensive care unit - Karagiannis, Panagiotis; Klingler, Felix; Arelin, Viktor; Alsdorf, Winfried; König, Christina; Roedl, Kevin; Fiedler, Walter; Weisel, Katja; Kluge, Stefan; Bokemeyer, Carsten; Wichmann, Dominic (Frontiers in Oncology, 2025)
ObjectiveAnalyze the outcomes of critically ill patients who developed new-onset organ dysfunction and received systemic chemotherapy during their ICU stay.DesignRetrospective cohort study.SettingA tertiary medical center in Germany with an Intensive Care Medicine department consists of 11 intensive care units comprising 140 beds, serving all subspecialties of adult intensive care medicine.Patients167 patients receiving systemic oncological treatment from January 1st, 2015 to December 31st, 2021, with a data cut-off on December 31st, 2022.InterventionsNone.Measurements and main resultsA total of 167 patients were included. The primary reasons for ICU admission were respiratory failure and shock/sepsis, each accounting for 34% of cases, while complications associated with oncological therapy accounted for less than 8%. The median age of hematological patients (n = 129) was 62 years (IQR 50–70), and for solid tumor patients (n = 38), it was 60 years (IQR 52–65). Predominant disease entities included lymphoma (43%) and acute myeloid leukemia (29%) among hematological patients, and lung cancer (47%) and gastrointestinal malignancies (17%) among solid tumor patients. Hematological patients had a significantly higher median Simplified Acute Physiology Score II (47 vs. 39 points; p=0.013), a higher need for invasive mechanical ventilation (59% vs. 50%; p=0.3), renal replacement therapy (54% vs. 24%; p < 0.001), and a higher 1-year mortality rate (64% vs. 53%; p=0.2) compared to solid tumor patients. The hazard ratio for 1 year survival for male sex was 2.34 (1.31–3.49), for mechanical ventilation 2.01 (1.33–3.04), for vasopressor therapy 1.98 (1.27–3.10), and for renal replacement therapy 1.51 (1.03–2.23), respectively.ConclusionAdministering intravenous chemotherapy in an ICU setting remains challenging, and the experience to establish an indication for systemic chemotherapy is still challenging. However, the study demonstrates that, after careful interdisciplinary decision-making, a substantial number of patients can benefit from it.